Enhancing radar applications: FPGA-driven phase estimation with floating point arithmetic - Sivaprasad, Ponduri; Venkataraman, Anandi; Murty, P Satyanarayana (Institute of Advanced Engineering and Science, 2024)
This article introduces a paradigm shift in radar technology with field programmable gate array (FPGA)-driven Phase estimation using floating point arithmetic (FPA). Leveraging FPGA’s parallel processing and the precision of FPA, this work promises enhanced accuracy and efficiency. The proposed system’s key performance metrics include the following: number of slices: 20,941, number of look-up tables (LUTs): 22,371, number of digital signal processing (DSP) blocks: 2, delay: 112.9 ns, and power consumption: 7.2 mw. A comparative analysis showcases advantages in area utilization, LUT, and DSP blocks despite a trade-off with delay. The presented methodology and results demonstrate the feasibility of real-time phase estimation at GHz rates, positioning this approach as transformative for next-gen radar systems.